Strategies for Managing Renovation Project Delays: An Integrated Approach to Project Communication and Stakeholder Engagement Using the Critical Path Method. - Karmawan, Indra (Publisher Cv. Inara, 2025)
Delays in hotel renovation projects can significantly disrupt business continuity, increase operational costs, and erode stakeholder confidence. This study investigates the primary causes of delay and the role of stakeholder influence in managing renovation projects, focusing on the Hotel X Jakarta renovation case. A mixed-method approach was adopted, combining quantitative analysis through questionnaires and Exploratory Factor Analysis (EFA), along with qualitative insights from stakeholder interviews. Fifty respondents representing both internal and external actors were selected from a total of 100 identified project stakeholders. The findings revealed three dominant causes of delay: (1) ineffective communication and coordination among project teams, (2) decision-making delays by internal managerial staff, and (3) lack of involvement of key stakeholders in the early phases of the project. The most influential contributors to delay were internal decision-makers, government regulators responsible for permitting, and external consultants who failed to deliver project documentation on time. Stakeholder mapping showed that these actors possessed both high power and high interest, yet their engagement was either misaligned or delayed. These results indicate that project delays are not only technical issues but are also deeply rooted in behavioral, organizational, and structural dynamics. To mitigate such delays, renovation projects should integrate stakeholder engagement strategies with proactive communication planning and scheduling tools such as the Critical Path Method (CPM). This integrated approach provides a more resilient framework for managing complexity in multi-stakeholder renovation environments.